ANALISIS KELAYAKAN OBJEK WISATA DANAU RAYO KABUPATEN MUSI RAWAS UTARA - SOBIRIN, AMRIN; Mariya, Sri (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
This study aims to (1) Describe the Potential of Rayo Lake Tourism Object in North Musi Rawas Regency, (2) Analyze the feasibility or ineligibility of Rayo Lake tourism object potential in North Musi Rawas Regency. The research method used is a mixed method. Data collection is done by observation, interviews and documentation. The technique of selecting the sample of people interviewed by purposive sampling and accidental sampling techniques. Data analysis was carried out with reference to the Guidelines for Analysis of Operational Areas for Natural Tourism Objects and Attractions ADO-ODTWA Director General of PHKA 2003 according to the values determined for each criterion. The results of research conducted on the potential in Lake Rayo, Musi Rawas Utara Regency are the potential for natural scenery, flora and fauna, and cultural tourism, in the ADO-ODTWA analysis of the Director General of PHKA 2003 with several indicators of attractiveness, accessibility, accommodation, supporting infrastructure, water clean, and security obtained a value of 83.3%, in conclusion the Lake Rayo tourist area is feasible to be developed as a tourist attraction area.